Pelatihan Menulis Cerpen untuk Meningkatkan Kreativitas Siswa Madrasah Tsanawiyah - Eti Sunarsih; Gunta Wirawan; Safrihady; Wahyuni Oktavia; Zulfahita; Sri Mulyani; Lili Yanti; Sovia Nur Havizah (Universitas Pamulang, 2025)
Students at MTs Ushuluddin Singkawang face several challenges in learning the Indonesian language, particularly in writing literary works. Based on observations and interviews, it was found that most students have low self-confidence, limited literacy skills, and a lack of creativity in expressing ideas through writing. Their written works generally consist of summaries of lesson materials rather than creative literary pieces such as short stories. To address these issues, the implementation team carried out a Community Service Program (PkM) in the form of a short story writing workshop aimed at enhancing students’ creativity, literacy skills, and self-confidence in literary writing. The workshop was conducted through four main stages: (1) preparation, including material development, coordination with the school, and participant selection; (2) training implementation, involving the delivery of short story writing techniques and hands-on practice; (3) mentoring for story production, providing guidance in drafting and revising students’ works; and (4) evaluation through assessment of the final works and measurement of improvement using pretests and posttests. A total of 27 students from class VIIIC participated in this activity. The results showed a significant improvement in students’ short story writing skills, with 77.8% achieving a “very high” category and 22.2% achieving a “high” category. Participant satisfaction was also high, with 92.59% expressing they were “very satisfied” and 7.40% “satisfied” with the program. Although some students still struggled with spelling and mechanics, overall the workshop effectively enhanced students’ understanding, motivation, and self-confidence in creative writing. Therefore, the short story writing workshop proved to be an effective means of developing students’ creative potential while strengthening the culture of literacy in schools..